Health morbidity and access to services by young adults with Down syndrome. (January 2014) - Prasher, Vee P.; Glenn, Sheila; Cunningham, Cliff; Arshad, Humaira; Glenholmes, Patricia; Kirby, Adam
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: Health morbidity in children and older adults with Down syndrome (DS) is relatively well established, but morbidity in young DS adults has not been specifically researched. Methods: This study undertook health assessments in 130 young adults with DS investigating physical, psychiatric, and access to services in a representative population of young adults with DS. Results: The study found a comparable prevalence of both physical and psychiatric morbidity in the young population with historically improved access to services, although further improvement was highlighted. Conclusion: The study highlighted the need for increased health surveillance in young adults who, similar to children and older adults with Down syndrome, are at risk of high rates of health morbidity.